2014
DOI: 10.1161/hypertensionaha.114.03275
|View full text |Cite|
|
Sign up to set email alerts
|

Estrogen Metabolism by Cytochrome P450 1B1 Modulates the Hypertensive Effect of Angiotensin II in Female Mice

Abstract: To determine the role of CYP1B1 in the gender difference in response to Ang II-induced hypertension, female Cyp1b1+/+ and Cyp1b1−/− mice were infused with Ang II (700 ng/kg/min) or vehicle with/without ovariectomy. In addition, mice were treated with the CYP1B1 inhibitor, 2,3′,4,5′-tetramethoxystilbene (TMS, 300 μg/kg, every 3rd day, i.p.), and 17-β-estradiol metabolites, 2-hydroxyestradiol (2-OHE), 4-OHE, or 2-methoxyestradiol (2-MeE2) (1.5 mg/kg/day, i.p., for 2 weeks), and systolic blood pressure (SBP) meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 57 publications
(72 reference statements)
2
68
2
1
Order By: Relevance
“…In support of this concept, we observed that 2-ME, but not H-1152, inhibits PDGF-induced ERK1/2 and Akt phosphorylation and that 2-ME, but not H-1152, downregulates PDGFinduced cyclin D1 and B1 expression. Consistent with our past (4) and present investigations, studies by Jennings et al (17) in mice provide additional evidence that endogenous 2-ME inhibits ERK1/2 and Akt phosphorylation. The results by Jennings et al, along with our findings, suggest that 2-ME, but not H-1152, downregulates the phosphorylation of proteins important for G 0 /G 1 progression.…”
Section: Discussionsupporting
confidence: 93%
“…In support of this concept, we observed that 2-ME, but not H-1152, inhibits PDGF-induced ERK1/2 and Akt phosphorylation and that 2-ME, but not H-1152, downregulates PDGFinduced cyclin D1 and B1 expression. Consistent with our past (4) and present investigations, studies by Jennings et al (17) in mice provide additional evidence that endogenous 2-ME inhibits ERK1/2 and Akt phosphorylation. The results by Jennings et al, along with our findings, suggest that 2-ME, but not H-1152, downregulates the phosphorylation of proteins important for G 0 /G 1 progression.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, in female mice, the CYP1B1-generated estradiol metabolite 2-methoxyestradiol is protective against Ang II hypertension, and estradiol ameliorates Ang IIeinduced AAA. 59,60 Our preliminary results indicate that CYP1B1 and 2-methoxyestradiol are protective against Ang IIeinduced AAA in female Apoe À/À mice (Thirunavukkarasu and Malik, unpublished work). Therefore, our study has important translational implications and suggests that the development of selective inhibitors of CYP1B1, such as TMS, could be useful in treating AAA associated with increased activity of the renineAng system in males, but could be detrimental in females.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, miR-27b levels are significantly upregulated by a high-fat diet and hepatic miR-27b and its target genes are inversely altered in a mouse model of dyslipidemia and atherosclerosis (Vickers et al, 2013). Whether CYP1B1 is involved in the latter is unclear, but the enzyme was recently linked with protection against angiotensin II-induced hypertension in female mice (Jennings et al, 2014).…”
Section: A Regulation Of Cytochrome P450 Enzyme Expression and Activitymentioning
confidence: 99%
“…CYP1B1. This enzyme is again worth mentioning briefly because the sex difference in the hypertensive response to angiotensin II in mice was recently attributed to the differential expression of CYP1B1 (Jennings et al, 2014). Indeed, CYP1B1 as an estrogen-metabolizing enzyme is more highly expressed in female than male mice and angiotensin II caused cardiovascular remodeling and endothelial dysfunction accompanied by oxidative stress in Cyp1b1 2/2 and ovariectomized Cyp1b1 +/+ mice but not in Cyp1b1 +/+ mice.…”
Section: Inflammation and Resolution Of Inflammationmentioning
confidence: 99%